Mengembangkan Keterampilan Berkomunikasi dan Pendidikan Karakter Bangsa Para Siswa di Sekolah Dasar - Gracia Sagita Silalahi; Gusti Pirandy (Yayasan Literasi Sains Indonesia, 2023)
In the world of education, communication skills and national character education are needed, especially in elementary schools. Communication is the process of transferring information, understanding, and understanding from someone, a place, or something to something, place or other people. The purpose of writing is to develop communication skills and national character education of students in elementary school. The location of the practice was carried out at UPT SDN 060809 Jl. Halat No. 48 Medan City. With class V students as many as 27 students, which lasted for 3 months. The method used in this practice is the groupwork method by Zastrow, with stages: (1) Engagement, Intake, Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The results of this practice show the development of communication skills of the students, and changes in the character of students for the better. At the beginning of the meeting, the students are difficult to make introductions in front of the class, and it is quite difficult to manage. After several meetings, the students began to dare to answer questions and make presentations in front of the class, also better at following the lesson.